Narodowe formacje wojskowe w Rosji bolszewickiej i Związku Sowieckim w latach 1918–1943 i ich rola w polityce ekspansji imperium - Jasiewicz, Krzysztof (Dzieje Najnowsze, 2016)
National Military Formations in Bolshevik Russia and the Soviet Union in 1918–1943 and Their Role in the Policy of Imperial Expansion National military units appeared in Bolshevik Russia already during the so–called October Revolution and predominantly the period known as the “Civil War” or the “Struggle against the Counter–Revolution”. It is highly probable that upon this stage in the history of Bolshevik Russia the existence of such armies was supposed to bolster the self–esteem of the vanquished nations and their elites and to preserve the mistaken conviction that Red Russia respected their right to self–determination and was devoid of imperial or Russification leanings. These armies, based on voluntary recruitment and during the winter even disbanded, resembled rather a Red militia, not to mention a commonplace gang. Nonetheless, the application of a national rhetoric made it easier to conceal the true Bolshevik targets, i.e. the reconstruction and even the expansion of the former tsarist Empire. It seems worthwhile to draw attention to a certain continuum of the Russian/Soviet or Putinesque line pursued by the Russian state and a strategic scheme planned at least decades ahead, regardless of its provenance. Today, the counterpart of the ”national” armies and governments involves ”independent” separatists and their military and political structures as well as long ago devised models of conduct (elections, plebiscites, rhetoric suitable for a presentation of arguments, etc.). Hence an analysis of former military–political conceptions may well serve contemporary objectives.